Myastehenia Gravis is Caused by the Thymoma in Anterosuperior Mediastinum Sinistra and Posteroinferior Sinistra - Irfan, Ferdy Syah; Djajalaksana, Susanthy (Malang Respiratory Journal, 2019)
Background: Thymoma is the most common thymus tumor; it covers 30% of the anterior mediastinum mass in adult. Almost half of thymoma does not present with any symptom and is found by accident. In 40% of patients have symptom of myasthenia gravis; other symptoms include chest pain, symptoms of bleeding and compression to other mediastinum’s structures. Ninety percent of thymoma is located in anterior mediastinum.Case: A 42-year-old woman came to Saiful Anwar Hospital with a complaint of difficulty in swallowing since three months before admission. We performed physical examination and chest X-ray AP’ and the result was within normal limit. In USG examination, there was no abnormality. From the laboratory examination, we found leucocytosis and from the CT-scan imaging, we found pocketed pleural effusion sinistra at the postero-inferior part.Based on these findings, we diagnosed (pre-operation diagnosis) this patient as anterosuperior mediastinum tumor: suspect thymoma. The pulmonologist consulted to Surgical Department for surgery. The surgeon performed sternotomy-tumor excision. The result from the vries coup and histopathogical examination was thymoma. FOB after the surgery showed an edema at the right vocal cord (post-extubation). Post-operative chest X-ray showed no mass in antero-superior mediastinum.